Pengembangan Produk Lembaran Buah (Fruit Leather) Jambu Air Dengan Fortifikasi Spirulina sp. - Mardiyana Mardiyana; Murni Handayani; Fadillah; Any Kurniawati (JURNAL AGROINDUSTRI HALAL, 2023)
Fruit leather is one of the fruit processing by drying fruit pulp (puree) in the form of thin sheets so that it is shaped like fruit leather. Fruit leather product development is done by adding small components to the product in order to have a higher nutritional value. This addition is known as fortification. One of the fortification agents that has complete nutritional content is Spirulina. The purpose of this study was to determine the best formulation of water guava fruit leather product development fortified with Spirulina by looking at consumer acceptance through sensory tests and looking at the nutritional content of the fruit leather product. The treatments in this study consisted of three, namely Spirulina fortification as much as 0.1%, 0.5%, and 1%. Based on statistical tests at the 5% significance level, it showed that Spirulina fortification in all treatments did not make a difference in the sensory assessment of texture, aroma, and taste attributes but made a difference in color attributes. The best formulation of Spirulina fortified water guava fruit leather product development that is accepted by consumers based on the results of the effectiveness test of consumer sensory assessment is a fruit leather product with a formula of 200 grams of water guava fruit pulp, 40 grams of sugar, 2 grams of CMC hydrocolloid, 15 mL of lemon water, and 1 gram of Spirulina powder. Spirulina fortification also increased the protein and fat content of guava fruit leather products.